A European equivalence scale for public in-kind transfers - Rolf Aaberge; Audun Langørgen; Petter Y. Lindgren (Statistics Norway, Research Department, 2022)
This paper introduces a theory-based equivalence scale for public in-kind transfers, which justifies comparison of distributions of extended income (cash income plus the value of public services) between European countries. We demonstrate the usefulness of the proposed equivalence scale in an empirical analysis of the effects of public health care, long-term care, education and childcare expenditure on estimates of income inequality and poverty for 24 European countries. The empirical results show significant effects of public in-kind transfers on the level of income inequality and poverty for all countries. Over the period 2006-2018, inequality and poverty estimates display rather different trends across European countries.
Keywords: D30; H40; I30; 330; Income distribution; poverty; equivalence scales; needs adjustment; public services; inkind transfers